Emerging and Recycling of Li-Ion Batteries to Aid in Energy Storage, A Review - Shammya Afroze; Md Sumon Reza; Kairat Kuterbekov; Asset Kabyshev; Marzhan M. Kubenova; Kenzhebatyr Z. Bekmyrza; Abul K. Azad (Recycling, 2023)
The global population has increased over time, therefore the need for sufficient energy has risen. However, many countries depend on nonrenewable resources for daily usage. Nonrenewable resources take years to produce and sources are limited for generations to come. Apart from that, storing and energy distribution from nonrenewable energy production has caused environmental degradation over the years. Hence, many researchers have been actively participating in the development of energy storage devices for renewable resources using batteries. For this purpose, the lithium-ion battery is one of the best known storage devices due to its properties such as high power and high energy density in comparison with other conventional batteries. In addition, for the fabrication of Li-ion batteries, there are different types of cell designs including cylindrical, prismatic, and pouch cells. The development of Li-ion battery technology, the different widely used cathode and anode materials, and the benefits and drawbacks of each in relation to the most appropriate application were all thoroughly studied in this work. The electrochemical processes that underlie battery technologies were presented in detail and substantiated by current safety concerns regarding batteries. Furthermore, this review collected the most recent and current LIB recycling technologies and covered the three main LIB recycling technologies. The three recycling techniques—pyrometallurgical, hydrometallurgical, and direct recycling—have been the subject of intense research and development. The recovery of valuable metals is the primary goal of most recycling processes. The growth in the number of used LIBs creates a business opportunity to recover and recycle different battery parts as daily LIB consumption rises dramatically.